2018
DOI: 10.1016/j.ijcard.2018.01.145
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus recommendations on the cardiogenetic care for patients with thoracic aortic disease and their first-degree relatives

Abstract: Age, family history, aortic size and syndromic features determine who is advised to have genetic testing as well as screening of first-degree relatives. There is a need for more prospective multicenter studies to optimize current recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 41 publications
0
47
1
2
Order By: Relevance
“…20 In patients with suspected MFS, the revised Ghent criteria should be employed as a high pre-test probability of disease confers 66-91% odds of finding an FBN-1 mutation and targeted FBN-1 testing should be pursued. 68 Tables 3 and 4 list the revised Ghent criteria. 69 However, if other familial TAAs are suspected, then the European Society of Human Genetics recommends testing for the following 'core genes': ACTA2, COL3A1, FBN-1, FLNA, MAT2A, MFAP5, MYH11, MYLK, NOTCH1, PRKG1, SMAD3, TGF-β2, TGF-β3, TGF-βR1 and TGF-βR2.…”
Section: An Approach To Diagnosismentioning
confidence: 99%
“…20 In patients with suspected MFS, the revised Ghent criteria should be employed as a high pre-test probability of disease confers 66-91% odds of finding an FBN-1 mutation and targeted FBN-1 testing should be pursued. 68 Tables 3 and 4 list the revised Ghent criteria. 69 However, if other familial TAAs are suspected, then the European Society of Human Genetics recommends testing for the following 'core genes': ACTA2, COL3A1, FBN-1, FLNA, MAT2A, MFAP5, MYH11, MYLK, NOTCH1, PRKG1, SMAD3, TGF-β2, TGF-β3, TGF-βR1 and TGF-βR2.…”
Section: An Approach To Diagnosismentioning
confidence: 99%
“…First-degree relatives (parents, brothers, sisters, and children) of patients with TAA should be screened because family studies have found an approximately 20% chance of another first-degree relative having a TAA. 3 Therefore, even if genetic testing does not reveal an identifiable mutation, first-degree relatives should have their aorta checked. An echocardiogram is usually recommended, especially in relatives of patients with Marfan syndrome or bicuspid aortic valve.…”
Section: Is Taa Inherited? What About Genetic Testing?mentioning
confidence: 99%
“…An important note regarding this definition of aortic dilatation is that this threshold is derived from cohort data of relatively young individuals with an age range from 9 to 59 years 5. Hence, this threshold of 40 mm6 may not be directly applicable to older individuals, especially given increasing evidence suggesting that aortic diameters change with age 7–9. Together with the finding that aortic complications mostly occur at older age,10 this emphasizes the need for data on the distribution of aortic diameters among older persons 11…”
Section: Introductionmentioning
confidence: 99%